Motivations and incentives: a comparative study - عياد عامر د.عبد القادر (Dirasat in Economics and Business, 2022)
The problem of motives and incentives is a problem that has perpetuated the capitalist system and will be with it as long as there is an exploiter and an exploiter. Despite the tremendous developments that occurred to narrow the gap between employers and producers, which was represented in reducing working hours, increasing security to protect producers, improving the work environment and issuing legislation that provides for the protection of producers, all of these solutions were reformist, not radical.